Nagaon Ke Rahasiye ( Hindi ) - Amish Tripathi (Chennai, India Westland Publications Limited, 2015)
The fabled Neelkanth, Shiva, is faced with his greatest challenge. He is forced onto a path of vengeance where nothing is as it seems, in The Secret of The Nagas (Shiva Trilogy). The hunt is on for a mysterious naga assailant who has taken the life of one of Shiva's close associates and now preys on his wife. This thirst for revenge will bring him face to face with the truth behind the mysterious nagas. The nagas are a deformed race of warriors with exceptional fighting skills, whose motives are hidden. They play a central role in a conspiracy that has brought a once mighty kingdom to its knees. And if Shiva is to break the deadlock, he must travel deep into hostile territory, where he will face a deadly adversary. At Kashi, Shiva's wife, Sati, who has recently given birth to their child, stays behind to help the King with an entirely different kind of battle. As Shiva's journey takes him away from her, she will uncover a secret that will change both their lives forever. Will Shiva and Sati's marriage survive, when the line between friend and foe becomes blurred?
Keywords: Hindi Books -- Hindi Books